1996
DOI: 10.1017/s135772980001506x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of terminal sire genotype, sex, slaughter weight, feeding regime and slaughter-house on growth performance and carcass and meat quality in pigs and on the organoleptic properties of fresh pork

Abstract: A total of 897 pigs were used in a study to investigate the relative effects of terminal sire genotype (lines Av.Bv. C), sex (castrate v. gilt), slaughter weight (80 v. 100 v. 220 kg), feeding regimen (ad libitum v. restricted, 0·82 ad libitum intake) and slaughter-house (HI v. H2 v. H3) on growth performance, carcass and meat quality characteristics and the eating quality offresh pig meat. Sire line A was a pure Duroc population, and B and C were European-type experimental lines where C contained Pietrain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
58
9
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(119 citation statements)
references
References 11 publications
44
58
9
8
Order By: Relevance
“…Gu et al (1992) indicated that the allometric coefficient of the carcass is .1 and; therefore, carcass yield is expected to increase with BW, consistent with the results of this experiment. An increase in SW from 106 to 122 kg BW increased carcass fat, which agrees with data of Cisneros et al (1996), Ellis et al (1996) and Latorre et al (2004). Trimmed ham yield decreased 0.10 percentage units per each 10-kg increase in SW.…”
Section: Carcass Traitssupporting
confidence: 88%
“…Gu et al (1992) indicated that the allometric coefficient of the carcass is .1 and; therefore, carcass yield is expected to increase with BW, consistent with the results of this experiment. An increase in SW from 106 to 122 kg BW increased carcass fat, which agrees with data of Cisneros et al (1996), Ellis et al (1996) and Latorre et al (2004). Trimmed ham yield decreased 0.10 percentage units per each 10-kg increase in SW.…”
Section: Carcass Traitssupporting
confidence: 88%
“…The LT muscle from gilts had lower lightness and redness than that from barrows but no difference was detected in water-holding capacity or tenderness, confirming previous reports (Cisneros et al, 1996;Ellis et al, 1996). Also, ham from barrows tended to have lower protein content than ham from gilts with no significant difference on IMF content.…”
Section: Meat Characteristicssupporting
confidence: 86%
“…However, gilts tended to have higher carcass yield than barrows, which agrees with Ellis et al (1996) and Latorre et al (2009), although other authors (Daza et al, 2010) did not find any difference. The discrepancies observed in the literature could be related to differences in the method used for trimming reproductive organs at the slaughterhouse.…”
Section: Carcass Characteristicssupporting
confidence: 82%
“…This was also found in some commercial crossbreeds with a significant effect of lower pH and a tendency to higher drip loss in females (Lloveras et al, 2008). It is generally accepted that the eating quality of pig meat (measured as tenderness, juiciness and flavour) is similar for castrates and females (Cisneros et al, 1996;Ellis et al, 1996;Leach et al, 1996). Storage effects.…”
Section: Genetic Variation In Meat Qualitymentioning
confidence: 63%